واقع تدريب معلمي اللغة العربية وسبل تطويره في جزر القمر:دراسة ميدانية على معلمى المرحلة الابتدائية - Ahmed Moidhini Moingarie; Kirembwe Rashid Abdul Hameed; Mohammad Najib Jaafar (worldconferences.net, 2024)
Non-Indexed Publication